Nativespeakerism and english teachers’pedagogical discourses (2020)
This research explored teachers’ and institutional pedagogical discourses regarding Nativespeakerism in an informal teaching setting in Bogotá through the analysis of semi-structured interviews. The purpose was to understand EFL teachers’ pedagogical discourses, their reconceptualizations, alienation and resistance attitudes, plus unveil power relationships when they face Nativespeakerism and the neoliberal discourse of standardization. This paper is framed within the Critical Applied Linguistics field and it attempts to approach the phenomenon under study from a poststructuralist perspective and the qualitative descriptive research (Merriam, 2019).